1998
DOI: 10.1086/515637
|View full text |Cite
|
Sign up to set email alerts
|

Early Prognostic Indicators in Primary Perinatal Human Immunodeficiency Virus Type 1 Infection: Importance of Viral RNA and the Timing of Transmission on Long-Term Outcome

Abstract: The time of perinatal human immunodeficiency virus type 1 (HIV-1) transmission and the pattern of early plasma viremia as predictors of disease progression were evaluated in infected infants followed from birth. Cox proportional hazards modeling demonstrated that a 1-log higher HIV-1 RNA copy number at birth was associated with a 40% increase in the relative hazard (RH) of developing CDC class A or B symptoms (P = .004), a 60% increase in developing AIDS (P = .01), and an 80% increase in the of risk death (P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…Indeed, in our study, most children who were infected in utero had relatively low levels of HIV-1 RNA at birth, as compared with initial positive HIV-1 RNA VL obtained in children who were infected later. This finding is consistent with previous studies conducted in industrialized countries (where a proportion of infants and their mothers during pregnancy received ARV treatment) 11,12 and in Africa as well. For instance, among 135 untreated children from Malawi, Biggar et al 24 obtained a median level in 24 cord blood-positive samples of 4.89 log 10 copies/mL, significantly lower than levels in the first positive samples of 52 cord blood-negative perinatally infected children (median: 5.55 log 10 copies/ mL).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, in our study, most children who were infected in utero had relatively low levels of HIV-1 RNA at birth, as compared with initial positive HIV-1 RNA VL obtained in children who were infected later. This finding is consistent with previous studies conducted in industrialized countries (where a proportion of infants and their mothers during pregnancy received ARV treatment) 11,12 and in Africa as well. For instance, among 135 untreated children from Malawi, Biggar et al 24 obtained a median level in 24 cord blood-positive samples of 4.89 log 10 copies/mL, significantly lower than levels in the first positive samples of 52 cord blood-negative perinatally infected children (median: 5.55 log 10 copies/ mL).…”
Section: Discussionsupporting
confidence: 93%
“…36 Despite the vast differences between subSaharan Africa and industrialized countries (in terms of viral, immunologic, environmental, and nutritional factors, and route of exposure including the additional risk linked to breastfeeding and access to ARV therapy), our findings corroborate and extend in a striking manner studies performed previously in the developed world 11,12,16,17 that observed a unique pattern of viral replication in infected children. In adults, during the period of primary infection, HIV-1 RNA copy number initially rises to high peak levels, rapidly followed by a 2-to 3-log 10 decrease until reaching a steady-state plateau (the virologic "setpoint") within approximately 6 to 9 months after the acquisition of HIV infection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The remaining infected children display a later onset of symptoms but nevertheless die within 5 to 10 years. Interestingly, most of these long-surviving children maintain a persistently high viremia and normal CD4 ϩ lymphocyte levels for many months following infection (1,10,35); this clinical picture sharply contrasts with the rapid clearance of HIV-1 viremia that is typical of adult infection. The sustained high-level viremia in infected children may result from persistent viral replication within the progressively expanding lymphoid cell mass (24), including the thymus, which represents the principal source of T lymphopoiesis during early life (15).…”
mentioning
confidence: 99%
“…P revious studies of HIV-1-infected infants have shown either the presence or absence of HIV-1 RNA at birth, and the magnitude and duration of early viremia are predictive of the long-term clinical outcome (1,2). The long-term survivors of perinatal HIV-1 infection are a special group of chronically infected children and adolescents critical to enhanced understanding of perinatal HIV-1 infection.…”
mentioning
confidence: 99%